Kerosene adulteration of tomato (Lycopersicom esculentum) - Manio, Mark Christian Carizon; Cornago, Djanna F. (2008.)
ABSTRACT The process of kerosene adulteration of tomatoes in distribution areas such as Divisoria, Balintawak and Pasig markets were documented. Information on the source of tomatoes, conditions of handling, purpose of adulteration and storage, quality preference of consumers as well as opinions of consumers on kerosene adulteration were obtained. The adulteration and storage practice was adopted in the laboratory. Tomatoes were stored at 20 to 24°C for a total of 10 days with analyses on the 1st, 4th, 7th and 10th day for color using tristimulus values (L*, a* and b*) and Munsell color notation parameters; color evenness and glossiness, and firmness using a defined score system; and sensory analyses using triangle test for appearance, firmness and odor; and intensity rating and acceptability test to measure overall acceptability, kerosene odor, color, color evenness, glossiness and firmness were conducted on the 4th, 7th and 10th day. There was an observed decreasing trend for L*, b* and firmness; increasing trend for a* and color evenness; and an increasing trend up to the 7th day and a decrease on the 10th day for glossiness. Significant discrimination in triangle test at α=0.05 was observed only for odor. Treatment did not affect overall acceptability and color evenness rating. A*, glossiness, ratings for kerosene odor, color, and glossiness were higher for the treated samples while L*, b*, firmness and its rating was lower. Kerosene odor showed negative relationship with acceptability, while color, firmness and glossiness showed positive relationship with acceptability. The results obtained from this study provided information on the practice of kerosene adulteration and its effects on the quality characteristics of tomatoes.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Food adulteration; Tomatoes